Grant's final victory : Ulysses S. Grant's heroic last year - Flood, Charles Bracelen (Cambridge, MA : Da Capo Press, 2011)
Recounts the last year of the former president's life, after losing his fortune, discovering he had cancer, and his race to complete his memoirs --
A change in fortune -- The man waiting for more bad news -- The lady at 3 East Sixty-sixth Street -- Retreat to New Jersey -- An opportunity -- To eat a peach, and soldier on -- Grant puts on his armor -- Mark Twain strides onto the stage -- Horses, and a last cigar -- A bittersweet Christmas -- Things come together -- Twenty years after the nation's great redemptive moment ; Reactions to a sick hero ; Unmarked anniversaries -- The "man of iron" keeps going -- Another loan from Vanderbilt -- Sunlight and shadow -- Good-bye, Ulyss. And thank you.
Includes bibliographical references (pages 269-274) and index.
Keywords: Grant, Ulysses S. -- 1822-1885 -- Last years; United States. -- Army -- Biography; Grant, Ulysses S. -- 1822-1885.; United States. -- Army; Grant, Ulysses S. -- 1822-1885.; United States. -- Army -- Biography; Presidents -- United States -- Biography; Generals -- United States -- Biography; Generals; Last years of a person's life; Presidents; United States; Presidents -- United States -- Biography; Generals -- United States -- Biography; Biographies; Biography; Biographies